A review about muscle focal vibration contribution on spasticity recovery - Fattorini, Luigi; Pettorossi, Vito Enrico; Marchetti, Enrico; Rodio, Angelo; Filippi, Guido Maria (Frontiers in Neurology, 2025)
IntroductionThis review analyses the benefits of focal muscle vibration (FV) in the treatment of spasticity enhancing current understanding and promoting sustained improvements in motor function. Findings could support the selection of optimal FV protocols, guide future research, and provide insights into the mechanisms by which FV may improve motor function in individuals with spasticity.MethodsA systematic search was conducted using the online databases PubMed, Web of Science, and The Cochrane Library. Including criteria: (a) participants presented with chronic spasticity; (b) the intervention involved the application of localized mechanical vibration; and (c) outcomes included neuromuscular functional parameters. Data extraction was performed independently by four reviewers, using a modified version of the 16-item Downs and Black checklist.ResultsA total of 20 studies were selected, most of which investigated on spasticity following stroke, as well as in conditions such as cerebral palsy, multiple sclerosis, and Minamata syndrome. FV effects were assessed using several methodologies: functional scales, digital analysis and electrophysiological evaluations. After-effects were positive and significant in 19 studies, while one study found non-significant results. In three studies, follow-up durations ranged between 1 and 30 days, and exceeded 1 month in seven. When adequate tests were performed, improvements extended to untreated muscles and involved complex motor behaviors.DiscussionThe after-effects of FV appear to be most relevant and long-lasting when a high-frequency (75–120 Hz), small-amplitude sinusoidal vibrations are repeatedly applied. The observed enduring improvements in complex motor behaviors suggest the involvement of sensory-motor mechanisms. These findings are discussed in the context of previous studies on FV.